Cross-Border cooperation in the European context: Evidence from regional cooperation initiatives. - Lorenz, Casimir; Egerer, Jonas; Gerbaulet, Clemens (Springer Nature, 2018)
Cross-border cooperation on energy policies is crucial for achieving the ambitious goals of the low-carbon transformation in Europe and the energiewende in Germany. Because the European electricity system is so densely interconnected, reform processes in one country affect the broader European market, whether through price effects, cross-border flows, or the sharing of backup capacity. Countries engaged in cross-border cooperation face the transaction costs of implementing new regulatory regimes and sometimes significant distributional effects. Spillover effects of investments in one country can be either positive or negative for neighboring countries. At the beginning of the low-carbon transformation process, Europe-wide coordination was the main driver of development, whereas today, regional cooperation among several neighboring countries plays an important role, and there are also cases of bilateral cooperation between countries over national energy policies. In this chapter, we analyze different forms of cooperation in the context of the European low-carbon transformation process and provide empirical evidence on some concrete cooperation schemes. The chapter focuses on regional cooperation schemes, as these provide plentiful evidence of developments and progress to date. Section 12.2 discusses potential fields of cooperation and specifies our classification of cooperation types. Section 12.3 focuses on the potential scope of regional cooperation in the electricity sector, and describes existing examples of cooperation, such as the Pentalateral Energy Forum (PLEF) and the North and Baltic Sea Grid Initiatives. Sections 12.4 and 12.5 provide model-based analysis of the concrete effects of regional cooperation: joint balancing markets in the Alpine region, and transmission expansion in the North and Baltic Sea Region. Section 12.6 draws lessons from the analysis and concludes.
Keywords: Energie; Energiewende; Internationale Zusammenarbeit; Windenergieanlage; Offshore; Energiespeicher; Stromnetz; Fallstudie; Kohleausstieg